Dynamic study on the anodic dissolution of 304 stainless steel with elastic stress in sodium chloride solution - Jiayue Zhou; Guangming Ding; Qincheng Li; Pengyu Yang; Yongyan Zhu (Electrochemistry Communications)
Effects of elastic stresses on the anodic dissolution of 304 stainless steel (SS) in 0.5 mol·dm−3 NaCl solution have been investigated by potentiodynamic polarization technique, scanning electron microscopy (SEM) and digital holography (DH). From the polarization curves, the SEM morphologies and the phase reconstruction maps, the effects of tensile and compressive stresses on the anodic dissolution of 304 SS have been analyzed. The tensile stresses and the large compressive stresses promote the anodic dissolution and increase the pitting susceptibility of 304 SS. However, the small compressive stress inhibits the anodic dissolution and decreases the pitting susceptibility of 304 SS. In this study, DH was used to observe the surface reactivity distribution of both the tensile and compressive stressed regions of the same sample. The conclusions obtained from the in-situ observations with DH are consistent with those drawn from the electrochemical measurements and the surface morphologies.